2001
DOI: 10.1580/1080-6032(2001)012[0008:aianco]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in autonomic nervous control of heart rate among tourists at 2700 and 3700m above sea level

Abstract: At 2700 and 3700 m, the activity of the autonomic nervous system measured by heart rate variability was decreased in untrained office workers. The sympathetic nervous system was dominant to the parasympathetic at 3700 m. These alterations in the autonomic nervous system might play some role in physical fitness at high altitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
39
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 26 publications
11
39
1
Order By: Relevance
“…During the hypoxic intervals, there was a substantial decrease in rMSSD, which supports the findings of other researchers (7,15,16,21). What was interesting, however, was the large variation in the individual HRV response to the IHE intervals (see Fig.…”
Section: Discussionsupporting
confidence: 90%
“…During the hypoxic intervals, there was a substantial decrease in rMSSD, which supports the findings of other researchers (7,15,16,21). What was interesting, however, was the large variation in the individual HRV response to the IHE intervals (see Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Increased sympathetic activity is a part of the integrated physiological response to a hypoxic stimulus (10,31). In the present study, we observed, in association with acute hypobaric hypoxia, an increase in heart rate, a reduction in R-R variability, and a relative increase of LF RR NU in asymptomatic subjects, consistent with a sympathetic predominance in the neural inputs to the heart and in agreement with previous studies conducted at high altitude (2,12,13). Little is known about the effect of AMS on the autonomic cardiovascular regulation.…”
Section: Cardiovascular Variability and Amssupporting
confidence: 93%
“…Although the HF rhythm primarily reflects the respirationdriven vagal modulation of sinus rhythm (32a), the nonrespiratory LF rhythm appears to have a widespread neural genesis (26) and, in normalized units (NU), apparently mainly reflects the sympathetic modulation of the heart (23, 26, 32a), as well as the baroreflex responsiveness to the beat-to-beat variations in arterial blood pressure (BP) (30). During exposure to high altitude, R-R variability is reduced with a relative increase in the LF component (2,12,13), suggesting an increased sympathetic modulation of the sinus node in response to hypobaric hypoxia. Little is known about whether this pattern is influenced and/or modified by AMS.…”
mentioning
confidence: 99%
“…1,2 Sympathetic overactivity with a relative reduction of parasympathetic activity has been found in untrained subjects. 3 Additionally, increased sympathetic activity occurs during exercise and much more so in untrained subjects. Furthermore, decreased baroreceptor activity has been demonstrated in healthy subjects at altitudes of approximately 4,500 m. 1 There is evidence that impaired autonomic function is associated with a significant risk for ventricular arrhythmias and sudden death in healthy subjects, 4 as well as in patients after myocardial infarction (MI).…”
mentioning
confidence: 99%